Analysis of the Utilization and Out‐of‐Pocket Costs of Authorized Generics and Independent Generics Among Medicare Beneficiaries - Arman Arabshomali; Kaustuv Bhattacharya; Sujith Ramachandran; Amit Patel; John P. Bentley (Health Services Research, 2026)
ABSTRACT Objective To assess the utilization trends of authorized generics (AGs) within Medicare, evaluate differences in out‐of‐pocket (OOP) costs for Medicare beneficiaries between AGs and independent generics (IGs) when both were simultaneously available in the market, and estimate the adjusted mean difference in OOP costs between these generic types while controlling for potential confounders such as benefit phase and Medicare plan. Study Setting and Design This retrospective analysis examined Medicare Part D claims from 2012 to 2020, focusing on prescription‐level OOP expenditures. Claims were limited to periods in which both AGs and IGs for the same product were concurrently available. Three measures of cost were used: per claim, per 30 units dispensed, and per 30‐day supply. Data Sources and Analytic Sample Using the 5% national Medicare Part D sample, linked to the FDA National Drug Code (NDC) Directory, AGs, IGs, and their market availability were identified. Plan information was retrieved from Medicare Plan Characteristics files. Sensitivity analyses applied winsorized OOP costs for outliers and a two‐part model for excess zeros. Principal Findings AGs comprised a small share of prescriptions and declined from 3.65% in 2012 to 2.30% in 2020. Compared to IGs, AGs incurred higher OOP costs across all measures. Median per 30‐day supply costs were $3.19 for AGs and $1.96 for IGs. Multivariable regression showed IGs had lower adjusted mean OOP costs, with differences of $4.32 per claim, $8.99 per 30 units dispensed, and $6.49 per 30‐day supply (all p < 0.0001). Results held across sensitivity analyses. Conclusions Despite their smaller market share, AGs are associated with consistently higher OOP costs than IGs. These cost differences have important implications for Medicare affordability and generic market competition. Policies that ensure timely independent generic market entry and prevent anticompetitive delay tactics may help reduce beneficiary financial burden and improve access to lower‐cost generics.